Consumer protection in microfinance services in mainland Tanzania: a critical analysis of the law - Lukuvi, Mossy (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the award of Degree of Master of Laws (Commercial Law) of Mzumbe University.